Pengaruh Model Circuit Learning (CL) Terhadap Keterampilan Berpikir Historis Siswa Pada Mata Pelajaran Sejarah Kelas XI Sma Negeri 3 Kota Tangerang - Alifia*, Nurbaiti; Fauzan, Rikza; Putra, Arif Permana (Universitas Syiah Kuala, 2024)
The objective of this study is to assess the impact of the Circuit Learning (CL) model on the historical thinking abilities of students in history education at State Senior High School 3 Tangerang City. The research methodology employed is quasi-experimental, utilizing purposive sampling as the sampling technique. The participants consisted of Class XI.2 as the experimental group and Class XI.3 as the control group. The research findings indicate a significant disparity in historical thinking abilities between the experimental group, which utilized the CL model, and the control group, which employed the discovery learning model. By analyzing the average scores obtained in the posttest, the experimental group achieved an average score of 38.42, while the control group using the discovery learning model obtained an average score of 30.95. A one-tailed t-test was conducted, resulting in the acceptance of the alternative hypothesis (Ha), as the calculated t-value for the experimental group (5.771) exceeded the critical t-value (1.997). In conclusion, there is a discernible discrepancy in the abilities of students between the experimental group utilizing the CL model and the control group employing the discovery learning model. Therefore, the utilization of the Circuit Learning model can enhance historical thinking skills among Grade XI students at State Senior High School 3 Tangerang City.Keywords: Learning Model, Circuit Learning, historical thinking skills